2023
DOI: 10.1093/nar/gkad020
|View full text |Cite
|
Sign up to set email alerts
|

Nearest-neighbor parameters for the prediction of RNA duplex stability in diverse in vitro and cellular-like crowding conditions

Abstract: RNA performs various spatiotemporal functions in living cells. As the solution environments significantly affect the stability of RNA duplexes, a stability prediction of the RNA duplexes in diverse crowded conditions is required to understand and modulate gene expression in heterogeneously crowded intracellular conditions. Herein, we determined the nearest-neighbor (NN) parameters for RNA duplex formation when subjected to crowding conditions with an ionic concentration relevant to that found in cells. Determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…18 We recently demonstrated that 40 wt % PEG 200 could mimic the molecular environment of cellular organelles. 30 Hence, the thermodynamic parameters of the designed hybrid duplexes were measured under typical cellular conditions in the S1). Experimentally observed ΔG°3 7 and T m values were compared in the presence and absence of the cosolute (Table S1), showing a reduction of thermal stability from dilute to crowded conditions, as observed for DNA duplexes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 We recently demonstrated that 40 wt % PEG 200 could mimic the molecular environment of cellular organelles. 30 Hence, the thermodynamic parameters of the designed hybrid duplexes were measured under typical cellular conditions in the S1). Experimentally observed ΔG°3 7 and T m values were compared in the presence and absence of the cosolute (Table S1), showing a reduction of thermal stability from dilute to crowded conditions, as observed for DNA duplexes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, we propose eq 7 to determine ΔG°3 7NN,[crowder] by adding the individual contributions to NN parameters by the major factors from the excluded volume effect (ΔG°3 7NN,ev ) and water activity (ΔG°3 7NN,wa ) of the cosolute by following our previous study. 30…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations